The role of growth factors in proliferation and invasion of thyroid cancer - Hölting, Thomas; Duh, Quan-Yang; Clark, O.; Herfarth, Christian (Oncology reports, 1997)
A growing literature has established the close association between tumor progression and growth regulatory aberrations in cancer cells. Most studies have focused on the phenomenon, that advanced tumors or metastases have lost the sensitivity to growth inhibitors. Metastasis are the primary cause of death in patients with differentiated thyroid cancer. Proliferation and differentiation of the thyroid was supposed to be under the major control of only a single hormone (thyroid stimulating hormone). However, we and others have shown that a complex network of various growth factors regulates growth and invasion of thyroid cancer cells. Our findings highlight two aberrations of growth regulation which may favour progression of malignancy and acquisition of metastatic competence: i) resistence to growth factor inhibitors and ii) growth autonomy of metastatic thyroid cancer cells.